The impact of door-to-electrocardiogram time on door-to-balloon time after achieving the guideline-recommended target rate - Lee, Chih-Kuo (PLoS One, 2019)
BACKGROUND: Little is known about the components and contributing factors of door-to-balloon time after implementation of Door-to-Balloon Alliance quality-improving (QI) strategies, including the impact of door-to-ECG time on door-to-balloon time. OBJECTIVE: We investigated whether modification of emergency department (ED) triage processes could improve door-to-ECG and door-to-balloon times after implementation of QI strategies. METHODS: This was a retrospective before-and-after study of a prospectively collected database. From June 2014 to October 2014, interventions were implemented in our ED, including a protocol-driven ECG initiation and moving an ECG station and technician to the triage area. The primary outcome was the percentage of patients with ST-elevation myocardial infarction (STEMI) who received ECG within 10 min of arrival; the secondary outcome was the percentage of patients with door-to-balloon times of <90 min from arrival. Patients from the year pre- and post-QI initiative were defined as the control and intervention groups, respectively. RESULTS: Enrollment comprised 214 patients with STEMI: 109 before the intervention and 105 after the intervention. We analyzed the components of the door-to-balloon process and found the door-to-ECG process was the most critical interval of delay (20.8%). Unrecognized symptoms were the most common cause of delay in the door-to-ECG process resulting in a significant impact on the door-to-balloon time. The intervention group had a higher percentage of patients with door-to-ECG times <10 min than did the control group (93.3% vs. 79.8%, p = 0.005), with a corresponding improvement in door-to-balloon times <90 min (91.1% vs. 76.2%, p = 0.007). In subgroup analysis, the intervention benefits occurred only in non-transferred or walk-in patients. After adjustment for possible co-variates, the QI interventions remained a significant contributing factor for achieving the door-to-ECG and door-to-balloon targets. CONCLUSIONS: The modification of ED triage processes through implementation of QI strategies are effective in achieving better door-to-ECG times and thus, achieving door-to-balloon times <90 min. In patients presenting with ambiguous symptoms, improved door-to ECG target achievement rates, through a protocol-driven and multidisciplinary approach allows for earlier identification of STEMI.